A novel potential primary method for quantification of enantiomers by high performance liquid chromatography-circular dichroism - Yi Luo (Nature Portfolio, 2018)
Abstract Primary methods play an important role in metrology. They can be used for the value assignment of certified reference materials, enabling the accuracy and comparability of the measurement. A novel potential primary method for enantiomer quantitation based on high-performance liquid chromatography-circular dichroism is described using L-phenylalanine as an example. The optimal quantitation range of L-Phe was from 0.1 mg/g to 1.2 mg/g, where both the relative bias and method variance were lower than 1%. The LOD and LOQ were 4 μg/g and 30 μg/g, respectively. The proposed method was also applied to the determination of the mass fraction of pure porcine insulin in solid. The average mass fraction obtained was 0.922 g/g with a RSD of 1.5%, and the associated relative uncertainty is 3.8% (k = 2), which agreed well with that obtained from the traditional isotope dilution mass spectrometry method. The LOD and LOQ for insulin quantitation were found to be 0.12 mg/g and 0.44 mg/g, respectively. The proposed method can be entirely described and understood by equations and a complete uncertainty statement can be defined in SI units.Therefore, it may be a potential primary method useful for the quantification of chiral compounds and proteins, and a supplementary method to the traditional isotope dilution mass spectrometry approach.